Effects of Anacardium Occidentale L. Leaf Extract on Serum Glucose Levels and Intestinal Glucose Absorption in Rats - Khoo, Mary Gaik Hong (2004)
The objective of this study was to verify the potential hypoglycaemic property of Anacardium occidentale L. vein and leaf aqueous extract in type 2 diabetic rat model. The rats were treated with the extracts (5, 50, and 500 mg/kg), which were incorporated into the drinking water and given daily for 6 weeks. Oral glucose tolerance test (OGlT) with 1.5 g/kg of glucose challenge was then performed to monitor the serum glucose level. An additional dose of their respective treatment was given again orally during OGTT to enhance the effect. The results did not show any improvement in the glucose tolerance even after 6 weeks of treatment, except for the positive control~lybenclamide. However, the serum glucose level rate of increase after oral loading with glucose was suppressed in the group treated with 500 m a g of the leaf extract. Glucose uptake into the blood was delayed by 46.81%, 33.02%, and 42.01% after 1, 3, and 6 weeks of treatment compared to before treatment. The same but milder effect was also seen in the 500 m a g of the veintreated group. The extract may have affected glucose absorption in the gastrointestinal tract. Therefore, another study was conducted to determine whether the extract has any significant effect on intestinal glucose absorption. In situ absorption technique according to Doluisio et al. (1969) was carried out. Kreb-Ringer phosphate buffer (KRPB) containing 7.5 mM glucose with or without the addition of A. occidentale L. leaf extract (1,5, 10, and 15 mg/ml) was then introduced into the lumen. Luminal samples were collected at various time intervals for glucose determination by GODPAP- method. 0.5 mM phlorizin was used as the positive control. The results showed that 10 mglml of the leaf extract inhibited glucose absorption in the jejunal segment of the experimental rats. Luminal glucose concentration was significantly higher at 5, 10, and 20 minutes than the control (95.32% vs. 68.91%, 79.71% vs. 45.97%, and 49.38% vs. 20.76% respectively), indicating less glucose was being absorbed. Nonetheless, the effect of 10 mg/ml could not beat the inhibition portrayed by phlorizin. At the same time, the leaf extract was also found to be able to interact with the standard blood glucose measurement [GOD-PAP-method], causing the measured value to be lower than the actual concentration. GOD-PAP-method is based on a simple oxidation reaction while the leaf extract was found to have high reducing power. The high reducing power of the leaf extract was believed to have counteracted the normal process of GOG-PAP-method, causing the values to be under-read. Nevertheless, the advantage of an extract with high reducing power is one could also be a good antioxidant. Thus, this study suggests that the aqueous leaf extract of A. occidentale L. might contain chemicals for treating diabetes mellitus by inhibiting intestinal glucose absorption. It may also exhibit antioxidant activity in biological system because of its high reducing power. This will be a good supporting therapy for diabetes as antioxidant has beneficial effects on glycaemic control and may help to ameliorate diabetes complications.